Taxonomic notes on desmids from the Netherlands - van Westen, Marien (Phytotaxa, 2015)
From the Netherlands, four desmid species are described as new to science: Cosmarium pseudodifficile, Cosmarium pseudoformosulum, Cosmarium pseudoreniforme, and Cosmarium turpiniiforme. Cosmarium jelskii was rediscovered after approximately a hundred years, Euastrum ansatum var. dideltiforme f. elongatum is raised to Euastrum ruzickae and Tetmemorus flensburgii is separated from Tetmemorus brebissonii. Differences with similar-looking species are discussed. In addition, zygospores of Staurastrum pileolatum are depicted for the first time.